Cognitive impairment among different clinical courses of multiple sclerosis. (October 2013) - Brissart, Helene; Morele, Elodie; Baumann, Cedric; Perf, Matthieu Le; Leininger, Matthieu; Taillemite, Laetitia; Dillier, Céline; Pittion, Sophie; Spitz, Elisabeth; Debouverie, Marc
Abstract : Background: As of yet, no consensus has been reached regarding cognitive impairment profiles in multiple sclerosis (MS) patients based on the MS type and disease duration. The main objective of this study was to describe cognitive impairment at the early stages of MS. The secondary objective was to compare cognitive performances in patients with relapsing remitting multiple sclerosis (RRMS), secondary progressive (SP) MS and primary progressive (PP) MS. Methods: The study included 128 MS patients and 63 healthy controls (HC). The study constituted five groups: early RR (ERR) (<3 years); late RR (LRR) (>10 years), SP, PP, and healthy Controls (HC). A neuropsychological assessment was performed including information processing speed (IPS), working memory, verbal episodic memory and executive functions. Results: Compared to HC, only impairment in phonemic fluency was observed in ERR. Slowing IPS, impairment in working memory and phonemic fluency were shown in LRR. In progressive forms, deficits were observed in verbal episodic memory, in working memory, in flexibility, in semantic and phonemic fluencies, with a slowing IPS. Conclusion: Verbal fluency is impaired at early stage of RRMS, in this form of MS, impairment increased with MS duration, and distinct cognitive profiles were observed between chronic and progressive forms.